2019
DOI: 10.1080/14697688.2019.1622295
|View full text |Cite
|
Sign up to set email alerts
|

Universal features of price formation in financial markets: perspectives from deep learning

Abstract: Using a large-scale Deep Learning approach applied to a high-frequency database containing billions of electronic market quotes and transactions for US equities, we uncover nonparametric evidence for the existence of a universal and stationary price formation mechanism relating the dynamics of supply and demand for a stock, as revealed through the order book, to subsequent variations in its market price. We assess the model by testing its out-of-sample predictions for the direction of price moves given the his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
145
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(175 citation statements)
references
References 36 publications
(28 reference statements)
9
145
0
Order By: Relevance
“…In [216], the authors used the limit order book time series data and LSTM method for trend prediction. The authors of [217] proposed a novel method that used limit order book flow and history information for the determination of the stock movements using LSTM. The results of the proposed method were remarkably stationary.…”
Section: Trend Forecastingmentioning
confidence: 99%
“…In [216], the authors used the limit order book time series data and LSTM method for trend prediction. The authors of [217] proposed a novel method that used limit order book flow and history information for the determination of the stock movements using LSTM. The results of the proposed method were remarkably stationary.…”
Section: Trend Forecastingmentioning
confidence: 99%
“…It is far from trivial to select informative features by hand. Recent research [11,10,14] has shown that deep learning models can deliver good predictive performance using only raw LOBs data with the process of feature extraction being automated by convolutional layers. However, such deep learning techniques are (typically) non-probabilistic and thus provide only heuristic uncertainty measures associated with output variables.…”
Section: Introductionmentioning
confidence: 99%
“…While numerous papers have investigated the use of machine learning for financial time series prediction, they typically focus on casting the underlying prediction problem as a standard regression or classification task [23,24,25,12,26,19,27]with regression models forecasting expected returns, and classification models predicting the direction of future price movements. This approach, however, could lead to suboptimal performance in the context time-series momentum for several reasons.…”
Section: Introductionmentioning
confidence: 99%